CFD modeling of a multichannel Fischer-Tropsch reactor module with microscale cooling channels: Effects of mirrored structure cooling layers - Woo, Yesol; Oh, Da Bin; Park, Jae Eun; Han, Seung Ju; Lee, Yun Jo; Park, Myung June (Korean Journal of Chemical Engineering, 2023)
Computational fluid dynamics (CFD) modeling of a multichannel Fischer-Tropsch reactor with microscale cooling channels is addressed in this study, wherein detailed mass, momentum, and energy balances were solved to retrieve detailed distributions of the conversion and temperature of both catalytic and cooling layers. A comparison between experimental data and simulation results showed relative errors of 6.73% and 1.22% for conversion and C5+ selectivity, respectively, which proves the validity of the proposed model. The novel structure of the reactor composed of mirrored structure cooling layers is suggested to prevent the thermal instability of a large-scale reactor module. The simulation showed that the symmetric distribution of the dense cooling channel area in the early part of the reactor decreased peak temperatures (ΔTmax=28.6 °C), whereas the nonmirrored case resulted in hot spots caused by the limited heat transfer capacity (ΔTmax=39.2 °C). The effects of the feed/coolant temperature, space velocity, and pressure were evaluated, and high temperatures and pressures resulted in a steep temperature increase in the early part of the reactor, whereas the high space velocity showed an increase in the area of peak temperature. Further, the analysis showed trade-offs of operating conditions between the conversion and selectivity of desired products.
Keywords: CFD Modeling; Fischer-Tropsch; Microscale Cooling Channels; Mirrored Cooling Layer; Multichannel Reactor